Information technology Metadata registries (MDR) Part 2: Classification = Technologies de l'information Registres de métadonnées (RM) Partie 2: Classification (ISO/IEC, 2019)
This document focuses on the part of the metadata registry (MDR) model called the classification region (see ISO/IEC 11179-3:2013, 9.2). The classification region permits the registration and administration of all or part of a classification scheme. A classification scheme can be used to classify a Classifiable Item (see ISO/IEC 11179-3:2013, 9.2.2.1), which is a type that can be applied to any metadata item in a metadata registry.